RE Protect-i / Mohd Azeem Ahmad Zaini ... [et al.] - Ahmad Zaini, Mohd Azeem; Fadzli, Farid Akmal; Mat Zahari, Mohd Saiful Izzat; Ahmad, Wahida; Mohammad Hatta, Mohammad Firdaus (2021)
Climate change is an inevitable and urgent global challenge with long-term implications for the sustainable development of all countries. As part of leading Islamic finance sector in the world, Malaysia can become a pioneer to become an environmentalist to contribute to the nature. Bank Negara Malaysia (BNM) issued a discussion paper on climate change and principle-based taxonomy in December 2019 as a guidance to facilitate financial institutions including takaful operators in identifying and classifying economic activities that can contribute to climate change objective. Malaysia is committed to reduce the carbon emission by 45% by 2030 in Paris Agreement 2016. Therefore, Takaful industry is not quite ready as it is almost not being discussed and it is not encouraging takaful operators to step up. The study aims to promote green environment via takaful product as well as to observe the viewpoints and potential demand on introduction of RE Protect-i in Malaysia. The study collected primary data via survey questionnaires from green energy consumers in Malaysia and secondary data including articles, books and internet resources. The finding of this study is that most of the green users in Malaysia realized the importance of RE Protect-i in Malaysia to improve climate change. In conclusion, RE Protect-i is one of the potential products from Islamic financial institutions (IFIs) and takaful operator that have a significant impact in promoting green environment in Malaysia as well as increase customer knowledge and awareness on the green environment through InsurTech or TakTech. The RE Protect-i gives a significant impact to climate change in Malaysia and helps takaful operators, regulators and policy makers to do further improvement and research related to product. Few studies have addressed the importance of green takaful to climate change which is big gap in the industry.